Flexible Surface Acoustic Wave Device with AlN Film on Polymer Substrate - Jian Zhou; Shurong Dong; Hao Jin; Bing Feng; Demiao Wang (Journal of Control Science and Engineering)
Surface acoustic wave device with c-axis-oriented aluminum nitride (AlN) piezoelectric thin films on polymer substrates can be potentially used for development of flexible sensors, flexible microfluidic applications, microsystems, and lab-on-chip systems. In this work, the AlN films have been successfully deposited on polymer substrates using the DC reactive magnetron-sputtering method at room temperature, and the XRD, SEM, and AFM methods reveal that low deposition pressure is beneficial to the highly c-axis-oriented AlN film on polymer substrates. Studies toward the development of AlN thin film-based flexible surface acoustic wave devices on the polymer substrates are initiated and the experimental and simulated results demonstrate the devices showing the acoustic wave velocity of 9000–10000 m/s, which indicate the AlN lamb wave.